2023
DOI: 10.3390/jcm12072466
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tailored Short Message Service (SMS) on Physical Activity: Results from a Three-Component Randomized Controlled Lifestyle Intervention in Women with PCOS

Abstract: This analysis of secondary outcome measures of a randomized controlled trial was conducted to study the effect of a one-year three-component (cognitive behavioural therapy, diet, exercise) lifestyle intervention (LSI), with or without additional Short Message Service (SMS) support, on physical activity and aerobic capacity in overweight or obese women with polycystic ovary syndrome (PCOS). Women diagnosed with PCOS and a BMI > 25 kg/m2 were randomly assigned to LSI with SMS support (SMS+, n = 60), LSI witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Previous studies in patients with PCOS have similarly reported that cognitive-behavioral interventions can reduce depressive scores in PCOS ( 35 , 44 , 45 ). Moreover, research has shown that using mobile applications and text messages as intervention measures can improve patients’ mental and physical health ( 22 , 46 ), which is consistent with our study findings. Furthermore, in our study, subgroup analysis based on study duration revealed a significant decrease in testosterone in the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies in patients with PCOS have similarly reported that cognitive-behavioral interventions can reduce depressive scores in PCOS ( 35 , 44 , 45 ). Moreover, research has shown that using mobile applications and text messages as intervention measures can improve patients’ mental and physical health ( 22 , 46 ), which is consistent with our study findings. Furthermore, in our study, subgroup analysis based on study duration revealed a significant decrease in testosterone in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, behavioral intervention has been applied and reported as a treatment option for PCOS patients (18). However, there is inconsistent evidence regarding the effects of behavioral interventions on body composition, clinical manifestations, and biochemical indicators in patients with PCOS (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Some studies suggest that behavioral interventions can lead to increased improvements in PCOS patients (20-28, 30, 31), while others have proved that behavioral interventions have no significant effect (29,32).…”
Section: Introductionmentioning
confidence: 99%
“…Sedentary performance is assessed as an additional area provided in minutes each week. This questionnaire was used to assess the physical activity of the subjects during a phase before the start of the protocol to ensure the immobility of the subjects [23]. PSS: The perceived stress was assessed via the 10-item PSS.…”
Section: Questionnairesmentioning
confidence: 99%